1976
DOI: 10.1128/jb.127.1.249-257.1976
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the transport of iron and the amount of specific colicin Ia membrane receptors in Escherichia coli

Abstract: Strains of Escherichia coli K-12 defective in their ability to utilize exogenously supplied iron due to genetic defects in the entF, tonB, fes, or fep gene exhibited elevated levels of the specific outer-membrane receptor for colicin Ia when compared with parental strains. Although entF, fes, and fep strains showed a higher degree of Ia sensitivity than did the parental strains, tonB strains were resistant to colicin action. The colicin insensitivity of tonB strains was not due to hyperproduction of enterochel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0

Year Published

1977
1977
1983
1983

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 24 publications
(33 reference statements)
0
22
0
Order By: Relevance
“…Both isolates were found to utilize ferric enterochelin as a source of iron and to be sensitive to colicin B and phage 480 vir and are, therefore, tonB+. Furthermore, in contrast to tonB mutants, which show enhanced levels of colicin Ia receptor due to iron stress (11), strains PW400 and PW402 bound little or no '"I-colicin Ia (data not shown). Indeed, colicin Ia resistance due to a defect in colicin adsorption is the classic phenotype defining cir mutants (3).…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…Both isolates were found to utilize ferric enterochelin as a source of iron and to be sensitive to colicin B and phage 480 vir and are, therefore, tonB+. Furthermore, in contrast to tonB mutants, which show enhanced levels of colicin Ia receptor due to iron stress (11), strains PW400 and PW402 bound little or no '"I-colicin Ia (data not shown). Indeed, colicin Ia resistance due to a defect in colicin adsorption is the classic phenotype defining cir mutants (3).…”
mentioning
confidence: 90%
“…It is concluded that the observed regulation by iron of the cir gene is under transcriptional control.The biosynthesis of enterochelin and the production of the outer membrane receptor specific for this phenolate siderophore are coordinately regulated by the amount of intracellular iron (2,9,10,12,15,16). In addition, the levels of two other outer membrane polypeptides seem to be similarly regulated: an 83,000-dalton protein with no known function and the 74,000-dalton cir gene product, which functions as the receptor for colicins Ia and Ib (2,(9)(10)(11)(12)15). It is known that the colicin I receptor is not required for ferric enterochelin transport (19).…”
mentioning
confidence: 99%
See 3 more Smart Citations